Making Liquid Soap from Cooking Oil Purification Results with Sugarcane Waste Adsorbent - Sovia, Ghina; Fauzi, Nurrohmat; Rizka, Rashinta; Pramudika, Satya; Paramita, Vita; Yulianto, Mohamad Endy (Journal of Vocational Studies on Applied Research, 2020)
Cooking oil is high enough economic value. Cooking oil is generally used to cook, but its uses are also many other than for cooking needs, such as skin beauty, lubricants and others. In the condition which the longer time, the price of cooking oil is higher than before, making some society to think creative by recycling the oil which has been used cooking oil. According to the research, it is know that sugarcane waste have strong adsorption potency to water content, and free fatty acid content that found in used cooking oil. The variable of this research are the rinsing time and the amount of sugarcane waste used. The best condition reaches to 40 gr sugarcane waste with the decrease water content reach 0.0050%; the rinse of sugarcane waste in 2x24 hours with free fatty acid intensity adsorption up to 0.23%